2001
DOI: 10.1063/1.1376141
|View full text |Cite
|
Sign up to set email alerts
|

Optical heterodyne magnetic rotation enhanced velocity modulation spectroscopy: A sensitive absorption-based scheme for paramagnetic molecular ions

Abstract: The sensitivity of velocity modulation spectroscopy (VMS) has been greatly improved by use of the frequency modulation enhanced magnetic rotation spectroscopic (FM-MRS) technique. This technique, which we refer to as optical heterodyne magnetic rotation enhanced VMS, has been described in detail in this article, including the experimental configuration, a discussion of line shape, and a systematic analysis of its sensitivity. N2+ has been used as a test sample of the technique, and the observed absorption spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The combined techniques of velocity modulation 17 and phase modulation 18 were used to improve the sensitivity. This method has been used in the visible region by Longsheng Ma and others at East China Normal University in combination with magnetic rotation for paramagnetic ions 62,63 and in the mid-infrared in this laboratory. 64 Figure 2 shows a schematic of our experimental setup, including the heterodyne detection electronics.…”
Section: Methodsmentioning
confidence: 99%
“…The combined techniques of velocity modulation 17 and phase modulation 18 were used to improve the sensitivity. This method has been used in the visible region by Longsheng Ma and others at East China Normal University in combination with magnetic rotation for paramagnetic ions 62,63 and in the mid-infrared in this laboratory. 64 Figure 2 shows a schematic of our experimental setup, including the heterodyne detection electronics.…”
Section: Methodsmentioning
confidence: 99%
“…High sensitivity is a critical aspect of any spectrometer used to study molecular ions, as the fractional ionization of a laboratory plasma is ∼1 ppm. This double modulation technique was developed independently by Longsheng Ma and others at East China Normal University and was used in combination with magnetic rotation to record the visible spectra of paramagnetic ions. , We have used this double modulation technique previously to study the visible spectrum of C 2 + , the near-infrared spectra of H 3 + and CH 2 + , and the infrared spectra of HCNH + .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Second, a method of using a double modulation scheme to remove the background signal in velocity modulation was developed by Lan et al Bidirectional velocity modulation was also developed as a method of eliminating optical pickup . Fourth, a technique using a magnetic field surrounding the positive column has been used, by Ma, to enhance the sensitivity of the absorptions of paramagnetic ions. , The fifth extension of velocity modulation, implemented by the Takagi group, was to the study HeH + and NeH + in the terahertz region. ,, Recently, ArH + and H 3 O + have also been studied in the terahertz region by Stephenson and Saykally with a setup very similar to those used at higher frequencies, showing the promise for extending velocity modulation below 100 cm -1 . Last, in the past year, velocity modulation has been successfully adapted for use in the submillimeter region (between ∼150 and 600 GHz, or ∼5−20 cm -1 ) by the Ziurys group. , …”
Section: History and New Developmentsmentioning
confidence: 99%
“…The finding was that the intensity of the N 2 + electronic spectra increased with increasing magnetic field strength, in agreement with previously observed behavior of the magnetic rotation effect for neutral paramagnetic species. In this particular case, however, there was another possible explanation for the enhancement, viz. that the magnetic field confines the electrons, increasing the plasma density. , However, Luo et al have shown that this confining effect results in only a small increase in sensitivity. Regardless of which mechanism made the biggest contribution to the signal increase, there was almost a 4-fold increase in S/N over the range from 100 to 500 G. This is a promising development for velocity modulation spectroscopy using intense laser sources with large background drifts.…”
Section: 4 Oh-mr-vmsmentioning
confidence: 99%
See 1 more Smart Citation